Conceptional cutting tool design for internal thread turning - Kiss, Dániel; Mihályi, Gergő (Design of Machines and Structures, 2020)
This article describes the different machining methods of the ball nut thread. One of the disadvantages of machining high pitch ball nuts by grinding process is to produce a modified tool profile to avoid collisions between the tool holder and the workpiece. However, by using profiled lathe inserts, it is possible to produce the thread profile of the ball nut using turning technology. The applicability of the technology is verified by tooling and experimental machining based on conceptual designs, the results of which are described at the end of the article.